SCHMIDT’S SYNDROME IN A 32 YEARS OLD FEMALE - Khattak, Abdul Latif; Ali, Waqar; Saleem, Salman; Idris, Muhammad; Khan, Naseer Ahmad; Pasha, Waseem (Journal of Ayub Medical College Abbottabad, 2015)
In polyglandular autoimmune (PGA) syndromes, there is immune dysfunction of two or more endocrine glands. Immunity mediated disorders of non-endocrine organs may also be seen. These syndromes are of two main types: type I and type II. We are reporting this case of a 32 years old lady who presented initially with hypothyroidism for many years and received thyroid replacement therapy. After that she was married and had children. After an interval of about seven years of the initial diagnosis of hypothyroidism, she was hospitalized in first trimester of pregnancy for severe vertigo, syncopal episodes and hypotension. She responded well to intravenous fluids and steroids. Further endocrine related investigations revealed Addison’s disease and the above episode were retrospectively diagnosed as Addisonian crisis. Thus the patient was diagnosed as Schmidt’s Syndrome (Autoimmune polyendocrine syndrome type 2) since 2009. Keywords: Schmidt’s syndrome, autoimmune, Addison’s disease, hypothyroidism